SOBRESSEMEADURA EM TIFTON 85 MANEJADA SOB PASTEJO: ESTABELECIMENTO E PRODUÇÃO DE FORRAGEIRAS HIBERNAIS - Jezewski, Tiago J.; Bergoli, Luís M. G.; Fernandes, Sandra B. V.; Maixner, Adriano R.; Uhde, Leonir T.; Londero, Ana L. (Salão do Conhecimento, 2013)
Resumo